Creating service excellence through Human Resource Management practices - Victoria Browning (South African Journal of Business Management, 1998)
Service excellence has become a critical source of competitive advantage for organisations. This article focuses on the interaction between the frontline employee and the customer and the role of Human Resource Management (HRM) in sustaining service-orientated behaviour. The nature of the relationship between HRM and service behaviour is also explored, focusing on three possible intervening variables - commitment to customer service, job competence and organisational identification. The implications of this relationship for business managers are highlighted and it is suggested that to achieve service excellence, managers need to focus as much on their internal relationships with employees as they do on their external relationships with customers, as their contribution to organisational performance is inter-linked. Directions for future research in redefining HRM practices and determining the nature of the link between HRM and service-orientated behaviour are discussed.
Keywords: 650